Bayesian statistics 4 : proceedings of the fourth Valencia international meeting : dedicated to the memory of Morris H. DeGroot, 1931-1989 - International Meeting on Bayesian Statistics (Valencia, Spain 15-20 April,1991); Bernardo, J. M.; Berger, J. O.; Dawid, A. P.; Smith, A. F. M. (United States : Oxford university press, 1992)
The proceedings of the 4th Valencia International Meeting on Bayesian Statistics, presented in this book, reflect state-of-the-art developments in the theory, application and computation of Bayesian methods.
I. Invited Papers (with discussion): D.V. Lindley: Is our view of Bayesian statistics too narrow?; M.J. Bayarri & M.H. DeGroot: A "bad" view of weighted distributions and selection models; J.O. Berger & J.M. Bernardo: On the development of reference priors; J.M. Bernardo & F.J. Giron: Robust sequential prediction from non-random samples: The election night forecasting case; D.A. Berry, M.C. Wolff & D. Sack: Public health decision making: asequential vaccine trial; P.J. Brown & T. Makelainen: Regression, sequenced measurements and coherent calibration; A.P. Dawid: Prequential analysis, stochastic complexity and Bayesian inference; J.-P. Florens, M. Mouchart & J.-M. Rolin: Bayesian analysis of mixtures: Some results on exact estimability and identification; A.E.Gelfand, D.K. Dey & H. Chang: Model determination using predictive distributions, with implementation via sampling-based methods; J. Geweke: Evaluating the accuracy of sampling-based approaches to the calculation of posterior moments; J.K. Ghosh & R. Mukerjee: Non-informative priors; P.K. Goel, C.M. Gulati & M.H. DeGroot: Optimal stopping for a non-communicating team; S.E. Hills & A.F.M. Smith: Parameterization issues in Bayesian inference; J. Hodges: Who knows what alternativelurks in the hearts of significance tests?; J.B.Kadane & D.A. Schum: Opinions in dispute: the Sacco-Vanzetti case; R.E. Kass & E.H. Slate: Reparameterization and diagnostics of posterior non-normality; X.-L. Meng & D.B. Rubin: Recent extensions to the EM algorithm; C.N. Morris & S.L. Normand: Hierarchical models forcombining information and for meta-analyses; A. O'Hagan: Some Bayesian numerical analysis; D. Pena & G.C. Tiao: Bayesian robustness functions for linear models; A. Racine-Poon: SAGA: Sample assisted graphical analysis; R.M. Royall: The elusive concept of statistical evidence; M.J. Schervish: Bayesian analysis of linear models; N.D. Singpurwalla & S.P. Wilson: Warranties; D.J. Spiegelhalter & R.G. Cowell: Learning in probabilistic expert systems; I. Verdinelli: Advances in Bayesianexperimental design; L. Wasserman: Recent methodological advances in robust Bayesian inference; M. West: Modelling with mixtures; R.L. Wolpert & W.J. Warren-Hicks: Bayesian hierarchical logistic models for combining field and laboratory survival data; J.V. Zidek & S. Weerahandi: Bayesian predictive inference forsamples from smooth processes; J.F. Angers: B.P. Carlin & N.G. Polson: Monte Carlo Bayesian methods for discrete regression models and categorical time series; G. Consonni & P. Veronese: Bayes factors for linear models and improper priors; R.G. Cowell: BAIES - A probabilistic expert system shell with qualitative and quantitative learning; P. Dellaportas & D.E. Wright: A numerical integration strategy in Bayesian analysis; M. Farrow & M. Goldstein: Reconciling costs and benefitsin experimental design; S. French, R.M. Cooke & F. Voght; The use of expert judgement in the context of a postulated mathematical model; A. Gelman & D.B. Rubin: A single series from the Gibbs sampler provides a false sense of security; A. Gilio: Co-Coherence and extension of conditional probabilities; W.R. Gilks:Derivative-free adaptive rejection sampling for Gibbs sampling; F.J. Giron, L. Martinez & C. Morcillo: A Bayesian justification for the analysis of residuals and influence measures; M.A. G"omez-Villegas & P. Main: The influence of prior and likelihood tail behaviour on the posterior distribution; E. Gutierrez-Pena: Expected logarithmic divergence for exponential families; T.Z. Irony, C.A.B. Pereira & R.E. Barlow: Bayesian models for quality assurance; P.W. Jones:Multiobjective Bayesian bandits; M.B. Mendel: Bayesian parametric models for lifetimes; E. Moreno & L.R. Pericchi: Bands of probability measures: A robust Bayesian analysis; G. Parmigiani & N.G. Polson: Bayesian design for random walk barriers; M.E. Perez & L.R. Pericchi: Analysis of multistage survey as a Bayesian hierarchicalmodel; L.I. Pettit: Bayes factors and the effect of individual observations on the Box-Cox transformation; C.M. Queen & J.Q. Smith: Dynamic graphical models; J.M. Quintana: Optimal portfolios of forward currency contracts; A.E. Raftery & S.M. Lewis: How many iterations in the Gibbs sampler?; G.O. Roberts: Convergence diagnostics of the Gibbs sampler; S. Sivaganesan: An evaluation of robustness in binomial empirical Bayes testing; K. Solna: Incorporating prior knowledge in a Markovpoint process model; F. Spizzichino: Reliability decisiion problems under conditions of ageing; D.A. Stephens & P. Dellaportas: Bayesian analysis of generalised linear models with covariate measurement error; W.E. Strawderman: The James-Stein estimator as an empirical Bayes estimator for an arbitrary locationfamily; T.J. Sweeting: On asymptotic posterior normality in the multiparameter case; A. Thomas, D.J. Spiegelhalter & W.R. Gilks: BUGS: a program to perform Bayesian inference using Gibbs sampling; A.J. van der Merwe & C.A. van der Merwe: Empirical and hierarchical Bayes estimation in multivariate regression models; D.A. Wooff: [B/D] Works.
Keywords: Bayesian statistical decision theory -- congresses